2014
DOI: 10.1145/2666356.2594330
|View full text |Cite
|
Sign up to set email alerts
|

Race detection for event-driven mobile applications

Abstract: Mobile systems commonly support an event-based model of concurrent programming. This model, used in popular platforms such as Android, naturally supports mobile devices that have a rich array of sensors and user input modalities. Unfortunately, most existing tools for detecting concurrency errors of parallel programs focus on a thread-based model of concurrency. If one applies such tools directly to an event-based program, they work poorly because they infer false dependencies between unrelated events handled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Clearly, the precise modeling of the Looper component is a challenging task [20]. However, we found that our current data flow analysis successfully determines registration-callback pairs, even for those cases where the Android Looper is involved (e.g., onClick).…”
Section: Discussionmentioning
confidence: 87%
“…Clearly, the precise modeling of the Looper component is a challenging task [20]. However, we found that our current data flow analysis successfully determines registration-callback pairs, even for those cases where the Android Looper is involved (e.g., onClick).…”
Section: Discussionmentioning
confidence: 87%
“…Event race detection algorithms have also been developed for Android, using similar techniques as those targeting JavaScript, but with more sophisticated happens-before relations [5,9,19]. Adapting our technique to Android is an interesting opportunity for future work.…”
Section: Related Workmentioning
confidence: 99%
“…Races in event-based programs Event-based programs, such as web applications and other UI applications, suffer from data races that result from the non-deterministic execution order of event handlers. Recent work detects such races in web applications [29,33] and Android applications [18,22]. Other approaches filter potential harmful races by analyzing their effects on persistent state [27] and on the DOM [20].…”
Section: Ui-level Testingmentioning
confidence: 99%